Chemical Quality of Pool Water and Correlation Between Swimmers Behaviour with Dry Eyes Syndrome in Tws Swimming Pool Padangan, Bojonegoro - Elisa Dwi Pertiwi (JURNAL KESEHATAN LINGKUNGAN, 2018)
Supervision and management of pool water quality need special attention to prevent health disorders. There are chemical substances in pool water that categorized as irritant and will cause Dry Eyes Syndrome if being used excessively. The purpose of this study was to analyze pool water chemical quality as well as swimmers behaviour and its correlation with Dry Eyes Syndrome. This was an observational research with cross sectional study design. The population in this study was swimmer within 16 - 45 years old age range in 1 time chlorination period, with the sample of 75 respondents. Statistic analysis process was done by using Chi-Square Test. The results showed that in chlor remnant level measurement, some results were indicating that the level of chlor exceeded the maximum allowed threshold (> 0.5mg / l) while the rest less than the minimum threshold (<0.2 mg / l). Hardness meausrement results (CaCO3) pointed out that the average outcome was exceeding maximum allowed threshold (> 500 mg / l). Statistic test result indicated that there were 2 variables related to the incidence of Dry Eye Syndrome, knowledge (p = 0,037) and action (p = 0,035). In the conclusion, the result of pool water chemical quality measurement showed that some of pool water had not met the requirement in accordance to Ministry of Health Regulation Number 416 in 1990. Therefore it is important to conduct management and routine supervision of the swimming pool also perform health promotion to prevent Dry Eyes Syndrome in swimming pool surroundings.